2018
DOI: 10.1186/s13098-018-0380-z
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear dysfunction and microvascular complications in patients with type 1 diabetes mellitus

Abstract: Sensorineural hearing impairment has been associated with DM, and it is probably linked to the same pathophysiological mechanisms as well-established in microvascular diabetes complications. The study of otoacoustic emissions (OAEs) is useful to identify subclinical cochlear dysfunction. Therefore, the aim of this study was to evaluate the association between abnormal OAEs responses, diabetic kidney disease (DKD) and diabetic cardiac autonomic neuropathy (CAN). We performed a cross-sectional study with 37 type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Furthermore, the association between tinnitus and hypertension found in participants aged 20 to 39 is accompanied with an association of diabetes and hypertension as well. Diabetes has also been shown to cause microangiopathic degeneration damaging the stria vascularis of the cochlea leading to clinical hearing loss (24,25). Interestingly, Dehkordi et al showed that patients with hypertension and/or diabetes had some relief from their tinnitus when treated with gabapentin.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the association between tinnitus and hypertension found in participants aged 20 to 39 is accompanied with an association of diabetes and hypertension as well. Diabetes has also been shown to cause microangiopathic degeneration damaging the stria vascularis of the cochlea leading to clinical hearing loss (24,25). Interestingly, Dehkordi et al showed that patients with hypertension and/or diabetes had some relief from their tinnitus when treated with gabapentin.…”
Section: Discussionmentioning
confidence: 99%
“…Since the normal functions of hair cells require high levels of glucose and ATP for the modulation of hearing [42], the impairment of glucose metabolism related to diabetes mellitus (DM) might be associated with patients with hearing loss [43,44]. Previous studies have shown that the relationship between diabetes and hearing dysfunction [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Microvascular complications are common feature in both ARHL and dementia. Research suggests that diabetes mellitus, which is characterized by many microvascular complication, is a common risk factor for both hearing loss [ 82, 83 ] and dementia [ 3, 84 ].…”
Section: Mechanisms For the Relationship Between Arhl And Admentioning
confidence: 99%